THE STATE RESPONSIBILITY TO THE HUMAN TRAFFICKING VICTIMS FROM HUMAN RIGHT PERSPECTIVE - Any Suryani (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThe state responsibilities to the human trafficking victims is not suitable with the goals of Indonesian Republic that based on Pancasila and Constitution of Indonesian Republic. So it needs affirmation about the state responsibilities to the human trafficking victims from the human rights perspective since the form of responsibility, that is institutional, laws and regulations related with the human trafficking, reasons of the victims to demand the state responsibility and the state responsibility to the human trafficking victims of foreign citizen.keywords: State Responsibility, Human Trafficking Victims, Human Right